2014
DOI: 10.1055/s-0034-1368600
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Health-Related Quality of Life of Cervical Cancer Patients – A Comparison between the Wertheim-Meigs Operation and Total Mesometrial Resection (TMMR)

Abstract: !Introduction: The present study compares for the first time the standard therapy for cervical cancer in FIGO-stages IB-IIB, radical hysterectomy according to the Wertheim-Meigs operation, with the newly developed, nerve-sparing surgical technique, total mesometrial resection (TMMR) with regard to postoperative, health-related quality of life. Method: In the framework of a multicentre, retrospective cohort study a total of 110 cervical cancer patients were interviewed once by means of the European Organisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…11 Specifically, comparing patients an average of 2-4 years after either traditional radical hysterectomy (class III) or nerve sparing modified radical hysterectomy (class II), those who underwent nerve sparing modified radical hysterectomy had overall improved mean EORTC QLQ-C30 and CX24 scores and specifically significantly improved scores in physical function, role function, fatigue, pain, shortness of breath, appetite, and diarrhea. 38 Furthermore, 7 years following exclusively surgical treatment, cervical cancer survivors resembled race- and age-matched peers in regards to physical, mental, emotional, and sexual well-being. 20 However, global health status and functioning may continue to be reduced in survivors treated with radiotherapy.…”
Section: Methodsmentioning
confidence: 95%
“…11 Specifically, comparing patients an average of 2-4 years after either traditional radical hysterectomy (class III) or nerve sparing modified radical hysterectomy (class II), those who underwent nerve sparing modified radical hysterectomy had overall improved mean EORTC QLQ-C30 and CX24 scores and specifically significantly improved scores in physical function, role function, fatigue, pain, shortness of breath, appetite, and diarrhea. 38 Furthermore, 7 years following exclusively surgical treatment, cervical cancer survivors resembled race- and age-matched peers in regards to physical, mental, emotional, and sexual well-being. 20 However, global health status and functioning may continue to be reduced in survivors treated with radiotherapy.…”
Section: Methodsmentioning
confidence: 95%
“…Since there was only 1 clinical trial with comparable data of the mean time of first flatus and first defecation, which indicated anorectal function recovery, we couldn't meta-analysis these data [16]. Sexual function of cervical cancer survivors was often assessed via several kinds of validated questionnaires, including the FSFI Questionnaire, the Dutch Gynecologic Leiden Questionnaire, and the Functional Assessment of Cancer Therapy-Cervix (FACT-Cx) Questionnaire, the European Organization for Research and Treatment of Cancer, Quality of Life Questionnaire with the cervical cancer module (EORTC QLQ-CX24) [15,18,[34][35][36]. In order to extract comparable data on postoperative sexual function of cervical patients, we included 2 studies used the same FSFI questionnaire [15,18].…”
Section: Main Findingsmentioning
confidence: 99%
“…However, this study compared a group without adjuvant RT with a group in which 31% of the women received adjuvant RT which may bias this study, especially since the effect of adjuvant RT was not analyzed in a multivariate regression analysis. 34 Pieterse et al found no difference in urinary and bowel function at 12 and 24 months after nerve sparing or nonYnerve sparing surgery, but this study evaluated the effect of nerve sparing in the less radical WM procedure only. In the present study, the more extended WO technique was associated with significantly more urinary problems.…”
Section: Discussionmentioning
confidence: 90%